2005
DOI: 10.1074/jbc.m412247200
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Human Micro-RNA miR-125b Reveals That It Is Critical for the Proliferation of Differentiated Cells but Not for the Down-regulation of Putative Targets during Differentiation

Abstract: Micro-RNAs are small non-coding RNAs that regulate target gene expression post-transcriptionally through base pairing with the target messenger RNA. Functional characterization of micro-RNAs awaits robust experimental methods to knock-down a micro-RNA as well as to assay its function in vivo. In addition to the recently developed method to sequester micro-RNA with 2-Omethyl antisense oligonucleotide, we report that small interfering RNA against the loop region of a micro-RNA precursor can be used to deplete th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
222
2
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(240 citation statements)
references
References 46 publications
9
222
2
7
Order By: Relevance
“…Expression of some miRNA could be correlated with specific breast cancer biopathologic features, such as estrogen and progesterone receptor expression, tumour stage, vascular invasion, or proliferation index. High expression of human miR-125b seems to be present in differentiated cells or tissues [27]. It was observed that breast cancer primary Again, these data suggest an implication of miRNA in mammary gland biology.…”
Section: Mirna Are Differentially Expressed In Normal and Tumour Breamentioning
confidence: 78%
“…Expression of some miRNA could be correlated with specific breast cancer biopathologic features, such as estrogen and progesterone receptor expression, tumour stage, vascular invasion, or proliferation index. High expression of human miR-125b seems to be present in differentiated cells or tissues [27]. It was observed that breast cancer primary Again, these data suggest an implication of miRNA in mammary gland biology.…”
Section: Mirna Are Differentially Expressed In Normal and Tumour Breamentioning
confidence: 78%
“…Given the vulnerability of unmodified dsRNA to nucleases in vivo, this class of compound could probably only be used in privileged local environments, for example in the central nervous system. 57 If a disease phenotype is derived from abnormal inhibition of mRNAs caused by, for example, excessive expression of miRNAs, AMOs complementary to either the mature miRNA or its precursors 58 can be designed (Figure 1). The earliest report of miRNA inhibition using AMOs describes the microinjection of DNA oligonucleotides of the same length and complementary to the target miRNA into Drosophila embryos.…”
Section: Targeting Mirna Regulation With Oligonucleotidesmentioning
confidence: 99%
“…Cheng et al 65 applied a library of Me-AMOs to human cancer cell lines to screen for miRNAs potentially involved in cell growth and apoptosis. As an alternative to direct blockage of a particular miRNA, Lee et al 58 recently suggested Me-AMOs directed against the loop region of a miRNA precursor as tools to determine miRNA function in vivo.…”
Section: Targeting Mirna Regulation With Oligonucleotidesmentioning
confidence: 99%
“…However, upregulation of specific miRNAs, such as the mir-17-92 cluster described above, appears to be associated with oncogenesis (He et al, 2005b;Volinia et al, 2006). In addition, other miRNAs, including miR125b and miR-143, have been directly associated with the differentiation and proliferation of certain cell types (Esau et al, 2004;Lee et al, 2005). Finally, miRNA expression patterns may change when cells are treated with differentiation-promoting agents (Kasashima et al, 2004;Stegmaier et al, 2004), and recent studies have shown that undifferentiated human embryonic stem cells express certain miRNAs (Suh et al, 2004).…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…At least two examples already suggest that miRNA dysregulation may affect major oncogenes such as c-myc and RAS O'Donnell et al, 2005). Additionally, the recent successes of inhibition of miRNAs at the cellular level (Hutvagner et al, 2004;Meister et al, 2004;Lee et al, 2005) suggest the possibility of direct targeting of miRNAs that are amplified or upregulated in patient tumors.…”
Section: Future Applications and Potential Limitationsmentioning
confidence: 99%